Groove Goes the Distance: An Initial Inquiry into Jazz Music in Egypt - Gohar, Farida (AUC Knowledge Fountain, 2026)
Jazz music has been a historically contentious site of social, cultural, and political signification. From the violent subjugation that characterized its origins and aspirational freedom that animated its practice, to its transformation into a distinctly “American” music instrumentalized by the US State Department to counter Soviet influence, jazz’s capacity for the inscription of meaning is vast and regularly cause for debate. The particular configuration of jazz music in Egypt is no less complicated although seldom studied. This thesis ventures an initial mapping of the dynamics and negotiations that historically defined the initiation of “Egyptian” jazz, as well as the ones that characterize the contemporary Egyptian jazz scene. By taking as its subject three influential figures of Egyptian jazz music– Rashad Fahim, Salah Ragab, and Amro Salah, it offers a critical narration and analysis of their personal histories and jazz-related discursive sensibilities. What emerges in the process is a complex portrait of jazz music in Egypt, one that, above all else, can be characterized by a lacking sense of situated identity. Referencing archival material, one-on-one interviews, and fieldwork at the Cairo Jazz Festival, this thesis marks the first substantive step towards a critical study of jazz music in Egypt and offers substantial material for further research.